2022
DOI: 10.2147/ijgm.s331378
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA Signatures Associated with Ferroptosis Predict Prognosis in Colorectal Cancer

Abstract: Background: Currently, colorectal cancer has become a common gastrointestinal malignancy that usually occurs in the colon and rectum, and ferroptosis plays a vital role in the pathology and progression of colorectal tumors. Methods: A total of 627 patients (51 normal and 644 tumor samples) from The Cancer Genome Atlas (TCGA)-COAD and TCGA-READ were included in the study. Lasso and Cox's regression was employed to analyze the characteristic lncRNAs in colorectal cancer samples, and a distinctive prognostic mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 25 publications
4
22
0
Order By: Relevance
“…7 , the level of LAG3 expression was higher in the high-risk group compared to the low-risk group, demonstrating the potential effect of LAG3 on shaping the tumor immune microenvironment. This finding is consistent with a recently published study demonstrating that the expression level of LAG3 in colorectal cancer is tightly associated with the levels of AC124067.4, AL137782.1 and AC010973.2 which are involved in our models [ 39 ]. These results indicate a potential functional link of those lncRNAs to LAG3 expression.…”
Section: Discussionsupporting
confidence: 94%
“…7 , the level of LAG3 expression was higher in the high-risk group compared to the low-risk group, demonstrating the potential effect of LAG3 on shaping the tumor immune microenvironment. This finding is consistent with a recently published study demonstrating that the expression level of LAG3 in colorectal cancer is tightly associated with the levels of AC124067.4, AL137782.1 and AC010973.2 which are involved in our models [ 39 ]. These results indicate a potential functional link of those lncRNAs to LAG3 expression.…”
Section: Discussionsupporting
confidence: 94%
“…Among the 17 lncRNAs related to m7G identified in our study, only AL137782.1, AC012313.5, AL031985.3, AC007728.3 and AC099850.4 are protective factors, but the other lncRNAs were risk factors. Consistent with our results, Previous reports have shown that AC133540.1, AL137782.1, AP001619.1, AC013652.1, AC008760.1, ALMS1-IT1, AC012313.5, FGF14-AS2, AP006621.2, LINC00702, LINC02550 and AC083900.1 are associated with poor prognosis in CRC patients (Huang and Pan, 2019;Hou et al, 2020;Yu et al, 2020;Xu et al, 2021a;Li et al, 2021;Li et al, 2022), whereas AC007991.4, LINC02381, AL031985.3 and AC099850.4 were reported in the other cancer patients with poor prognosis (Jafarzadeh and Soltani, 2020;Zhang et al, 2020;Zhao et al, 2020;Wu et al, 2021). The other lncRNAs were initially discovered.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that upregulation of ALMS1-IT1 can promote lung cancer progression by mediating AVL9 activation of the cell cycle protein-dependent kinase pathway ( Luan et al, 2021 ). Li et al constructed a ferroptosis-related lncRNA prognostic signature that also included ALMS1-IT1 and found it to be strongly associated with poor prognosis in colon cancer ( Li et al, 2022 ). These findings validated the oncogenic properties of ALMS1-IT1 and are consistent with our results.…”
Section: Discussionmentioning
confidence: 99%